Frequency of Foot Pain and Assessment of Foot Function Associated with Wearing Point Shoes in Students and Faculty Members of Fashion Designing Schools: Foot Pain and Assessment of Foot Function - Majeed, Rabia; Akbar, Muhammad Ammar; Waseem, Maheen; Zehra, Samer; Shaukat, Mamoona (Pakistan Journal of Health Sciences, 2023)
Pointed footwear inclines to remain trendy in the field of fashion design and causes discomfort and difficulty with daily activities. Objective: To determine and evaluate frequency of foot pain and assessment of foot function associated with wearing pointed shoes in students and faculty members of fashion designing schools. Methods: This cross-sectional study was conducted on fashion designing students and faculty members from December 2022 to May 2023 in Lahore, Pakistan. 396 participants between the ages of 18 and 50, of both genders with a minimum of 3 hours to a maximum of 8 hours wearing pointed shoes were included. Those with foot deformities or previous foot trauma were excluded. Foot and Ankle Ability Measure (FAAM) and Visual Analogue Scale (VAS) of pain were used. SPSS 25 was used for data analysis. Results: 51.52% reported moderate pain in their feet on Visual Analogue Scale, 30.81% people reported mild pain. 7.32% had no pain and 10.35% complained of severe foot pain. Chi-square test resulted in (110.859) and p-value of less than 0.05. Conclusions: The study concludes that wearing pointed shoes causes mild to moderate foot pain whereas significant impact was observed in their activities of daily living.